The modern Japanese print; an appreciation - Michener, James A. (Charles E. Tuttle Company, 1968)
1962 This book appeared as a limited edition of 475 copies in imperial folio size. the paper was the finest of handmade Japanese vellum, the binding, three colors of pure, fine weave hemp cloth. It is a book which the author takes considerable pride, for it is more than a book, it is a work of art.